PO 135 - SEGURANÇA E EFICÁCIA DO REMIFENTANIL EM CIRURGIA OFTAMOLÓGICA – ESTUDO PROSPETIVO - Maia, Nuno; Cruz, Margarida; Correia, Filipa; Sá, Steven; Cunha, Yacira; Bela, Lurdes (Journal of the Portuguese Society of Anesthesiology, 2023)
x